Identification Of Some Groups Active In Alhagi Plants And Pine Used In The Treatment Of Arthritis, Coughs And Colds - Hadi Kareem Dahaam; Amel Naji Wadi; Zainab Mahmood Abdulla (Journal of Madenat Alelem University College, 2015)
In this research extraction and Identification of chemical compounds (active substances) in the plant Alhagi and plant pine. Where the chemical extraction of these compounds using alcoholic solvents, then the diagnosis of these aggregates are effective in these plants using the equipment of chemical and spectral analysis, diagnostic and classical chemical methods.